Records of Representation: Clement Valla's Postcards from Google Earth - Jessica Becking (Media Theory)
This brief commentary explores images in Clement Valla's (2010-present) Postcards from Google Earth series from the vantage of aesthetics, landscape theory, and experience of the remote.